Good comprehensive performance of Laves phase Hf1-xTaxFe2 as negative thermal expansion materials. (December 2018) - Li, L.F.; Tong, P.; Zou, Y.M.; Tong, W.; Jiang, W.B.; Jiang, Y.; Zhang, X.K.; Lin, J.C.; Wang, M.; Yang, C.; Zhu, X.B.; Song, W.H.; et al.
Abstract: Negative thermal expansion (NTE) materials can compensate for the normal positive thermal expansion (PTE) of most materials, and thus have great potential applications. Itinerant magnetic Laves phase compounds Hf1- x Ta x Fe2 with x ∼0.16–0.22 exhibit an abrupt volume shrink as large as ΔV/V ∼1% at the ferromagnetic (FM) to antiferromagnetic phase transition. Here we report that by reducing the Ta concentration the sharp volume change was gradually modified to a continuous one and moved to room temperature. NTE was optimized in x  = 0.13, showing a linear NTE coefficient as large as −16.3 ppm/K over a broad window of 105 K (222 K - 327 K). As revealed by Electron Spin Resonance, the broadened NTE window is closely coupled with the asynchronous FM orderings of Fe moments at 6 h and 2 a Fe sites. In addition to good mechanical properties (i.e., Young's modulus, compressive strength and Vickers hardness), their thermal and electrical conductivities are superior to other metallic NTE materials, suggesting their wide applications as PTE compensators. Graphical abstract: Image 1